Molecular Evidence of the Inhibitory Potential of Melatonin against NaAsO2-Induced Aging in Male Rats - Maryam Baeeri (MDPI AG, 2021)
Arsenic (As) poisoning is widespread due to exposure to pollution. The toxic level of (As) causes oxidative stress-induced aging and tissue damage. Since melatonin (MLT) has anti-oxidant and anti-aging properties, we aimed to evaluate the protective effect of MLT against the toxicity of sodium arsenite (NaAsO2). Healthy male NMRI mice were divided into eight different groups. The control group received a standard regular diet. Other groups were treated with varying diets, including MLT alone, NaAsO2, and NaAsO2 plus MLT. After one month of treatment, biochemical and pathological tests were performed on blood, heart, and lung tissue samples. NaAsO2 increased the levels of TNF-α, 8-hydroxy-2-deoxy guanosine (8OHdG), malondialdehyde (MDA), reactive oxygen species (ROS), and high mobility group box 1 (HMGB1), increased the expression of TNF receptor type 1-associated death domain (TRADD) mRNA and telomerase reverse transcriptase, and decreased the expression of Klotho (KL) mRNA in both plasma and tissues. In contrast, MLT reduced MDA, ROS, HMGB1, lactate, and TNF-α enhanced the mRNA expression of KL, and suppressed the mRNA expression of the TERT and TRADD genes. Thus, MLT confers potent protection against NaAsO2- induced tissue injury and oxidative stress.